Evaluasi Pada Pengelolaan, Pemanfaatan, Dan Pelestarian Cagar Budaya Berkelanjutan Pada Situs Majapahit, Trowulan - Theodorus Aries Briyan Nugraha Setiawan Kusuma; Andika Witono; Andry Hikari Damai (Kemendikbud, 2021)
Archaeological remainin at Trowulan site, Mojokerto are one of the important assets in the world of Indonesia archaeology because it holds many valuable lessons from the past. Currently the Trowulan Site has not been able to show a big role for the wider community. This can be seen from the lack of awareness and socialization to the community. The problem raised in this study is how the implementation of management, utilization, and preservation is very necessary in establishing cooperation for the sustainability of archaeological remaining in heritage sites of the Majapahit Kingdom in Trowulan, Mojokerto. This study aims to see the implementation of the management, utilization, and preservation of the Majapahit Trowulan site as an archaeological site that has the potential to be developed. This study uses a descriptive analytic approach by observing the community around the Majapahit site in Trowulan. The data collection technique used a documentation study in the form of a map of the distribution of the Majapahit site in Trowulan and a literature study through previous research. The analysis used in this research is interactive analysis. The purpose of this study is to preserve the heritage sites of the Majapahit Kingdom by protecting the site such as rescue and security, zoning, maintenance and restoration for sustainable for generation to generation. These conservation efforts have been implemented but also still face a lot of obstacles such as human resources.